Nutritive value of marketable heads and outer leaves of white head cabbage cultivated at different nitrogen rates - Ryszard Kosson; Kazimierz Felczyński; Justyna Szwejda-Grzybowska; Maria Grzegorzewska; Lorenza Tuccio; Giovanni Agati; Stanisław Kaniszewski (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2017)
The effect of different nitrogen treatments (100–400 kg N ha−1) on yield and quality of marketable cabbage heads and outer green leaves (waste fraction) of two cultivars of Brassica oleracea convar. capitata var. alba L. grown in two years field experiment was studied. During harvest, the marketable cabbage heads and the outer leaves (not adjacent leaves of cabbage) were removed; total and marketable yield of cabbage were evaluated as well as nutritive value was determined based on content of some components, that is, dry matter, ascorbic acid, soluble polyphenols, total flavonoids, nitrates, total nitrogen and antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH). The study showed a significant effect of nitrogen fertilization on the total and marketable yield of the tested cultivars of cabbage. The weight of total cabbage heads was increasing according to higher nitrogen fertilization from 100 up 400 kg N ha−1 for both cultivars. The outer leaves of cabbage characterized by a significantly higher nutritive value compared with marketable head, which is supported by several-fold higher content of total flavonoids, soluble polyphenols and over the 100% increase in ascorbic acid content. Although the outer green leaves of cabbage are discarded after harvesting, they possess high nutritive potential which can be practically used or transformed into an added value product.